Operational Risk Management in Coffee Shop Business: an ISO 31000 Approach From Indonesia - Muhammad Zikri Akbar; Zenal Asikin; Raden Isma Anggraini (Indonesian Journal of Accounting, Risk and Governance, 2026)
Background: The rapid growth of the coffee shop industry in Indonesia has intensified competition and increased operational complexity for small and medium-sized enterprises in the food and beverage sector. Coffee shops rely heavily on daily operational processes involving human resources, equipment, supply chains, and service interactions. These operational dependencies create various risks that may disrupt business continuity if not managed systematically. Despite the growing number of coffee shop businesses, many small enterprises still lack structured operational risk management practices.Purpose: This study aims to analyze operational risk management in a coffee shop business by identifying operational risks, assessing their severity, and formulating appropriate risk mitigation strategies using the ISO 31000:2018 risk management framework.Design/methodology/approach: This research employs a qualitative descriptive approach using a case study of Kanca Coffee, a coffee shop located in Bogor, Indonesia. Data were collected through in-depth interviews, direct observation, and questionnaire surveys involving six internal respondents selected through purposive sampling. The analysis follows the ISO 31000 risk management process consisting of risk identification, risk assessment, and risk treatment. Risk assessment was conducted using the probability–impact method proposed by Godfrey, while risk treatment strategies were formulated based on the framework developed by Flanagan and Norman.Findings/Result: The results identified fifteen operational risks categorized into four main areas: internal process risks, human resource risks, system and technology risks, and external event risks. Risk assessment indicates that three risks fall into the low-risk category, six risks are categorized as medium risk, four risks as high risk, and two risks as extreme risk. The most critical risks include espresso machine malfunction, employee turnover, and raw material supply disruption. Risk treatment strategies proposed in this study include preventive equipment maintenance, employee training and retention programs, improved inventory management procedures, and the development of alternative supplier partnerships.Conclusion: The study demonstrates that the implementation of structured operational risk management can significantly improve operational resilience and service quality in coffee shop businesses. The application of the ISO 31000 framework provides a systematic approach for identifying operational vulnerabilities and developing effective mitigation strategies in small service enterprises.Originality/value (State of the art): This research contributes to the limited literature on operational risk management in the coffee shop industry by integrating ISO 31000 risk management principles with practical operational analysis in a small food and beverage enterprise. The findings provide managerial insights that may assist coffee shop managers in improving operational efficiency and long-term business sustainability. Keywords:operational risk management, coffee shop, ISO 31000, risk assessment, food and beverage SMEs